PENINGKATAN KEMAMPUAN PUBLIC SPEAKING PESERTA DIDIK MELALUI TEKNIK-TEKNIK KONSELING: SEBUAH KAJIAN LITERATUR - Nursilowati, Lilik; All Habsy, Bakhrudin; Nursalim, Mochamad; Budiyanto, Budiyanto (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
Public speaking is the skill of conveying information, messages, ideas or suggestions in front of a group of people with the aim of conveying information, influencing or entertaining. This research aims to describe counseling techniques that can be used to improve students' public speaking skills. The research method used in the research is literature study, namely by reading and reviewing various sources in the form of journal articles over a period of 5 years. The research results show counseling techniques that can be used to improve students' public speaking skills such as self-talk techniques, sociodrama, discussion, positive reinforcement, modeling, assertive training, and role play.